Literatura oral na escola pública: quebrando paradigmas, semeando saberes - Silveira , Bianca Farias da (2017)
The present study aims to demonstrate, from the presentation of a didactic-pedagogical proposal resulting from an experience report, the feasibility and the need to include oral literature as content of teaching and learning in the final years of elementary Municipal school Senador Ruy Carneiro, located in the neighborhood of Mandacaru, in João Pessoa-PB. In the process of construction of the proposal, three cultural producers from the neighborhood where the school is located: José Maciel de Sousa, master of Lapinha Jesus of Nazareth, José Elias do Nascimento, poet and playwright of popular culture and Vicente Bezerra de Macedo, a popularist known as Seu Gerson, who recounts the history of the emergence and development of the Mandacaru neighborhood since the 1930s. The socio-historical and cultural context in which Inserts the school, making possible the analysis of the forms of cultural manifestations shared by them, the collection of data, the crossing of information and a way of understanding cultural production in the midst of the social dynamics of the Mandacar community. It was also described the stages of the didactic-pedagogical proposal of insertion of the oral literature in the school curriculum of the final years of the elementary school, experienced in a gradual way, during four consecutive years. From a theoretical-methodological point of view, this work was developed through an action research. In order to mark the discussions, we used the orientations of Xidieh (1993), the techniques of interviews and testimony of Thompson (1992), the reflections related to the school curriculum, such as those of Silva (2000, 2004 and 2010) In the field of memory, such as those of Bergson (1990), Bosi (2010) and Halbwachs (2006), the specific research aimed at the manifestations of popular culture, like Ayala (1997, 2003 and 2011), Ayala and Ayala ( 2000), Bacalhao (2006) and Fernandes (2003). The results showed that the relationship between popular culture and school is tense. Both by the lack of knowledge of some teachers inherent in the peculiarities of the language in the oral mode, fundamental in the study of popular literature, as well as by the entrenched paradigms that popular culture is associated with the picturesque, exotic, linguistic "errors". Mediating the presence of cultural representatives in everyday school life was a way of confronting different experiences and ways of life, discussing in a natural and systematized way the ways of doing and living that transcend the history of the Mandacar people, breaking paradigms, sowing knowledge.